Effect of Drug on Tryptophan-Protein Binding in Plasma, Liver and Brain of Rabbit - SYEDA, TALAT; AZMAT, RAFIA; TALAT, RUKHSANA (Asian Journal of Chemistry, 2010)
Present study has been made to investigate the chronic ethanol treatment of rabbits, produced a decrease in total tryptophan concentration by 45.25 % in plasma, 32.58 % in brain and 3 % in liver respectively. The decrease in total tryptophan utilization in plasma may related to enhanced tryptophan utilization by brain or liver. The effect of tryptophan load on plasma, brain and liver was compared in controls and ethanol treated rabbits. The control and ethanol treated rabbits received an injection of tryptophan (500 mg/100 g body weight, imp.) 2 h before experimentation. Tryptophan concentration increased by 302.35 % in plasma, 809.64 % in brain and 552.80 % in liver. In the ethanol treated rabbits tryptophan loading caused an increase of total tryptophan concentration by 2121.65 % in plasma, 2191.63 % in brain and 695.55 % in liver. The results suggested the role and possible mechanism involvement in the metabolism of serotonin following ethanol treatment.